The wolf and the lion [videorecording (DVD)] - Maistre, Prune de, 1978-; Kunz, Molly; Greene, Graham, 1952-; Carrick, Charlie; Johns, Derek, 1992-; Slack, Rhys; Buliung, Evan (Breaking Glass Pictures, 2022)
A wolf pup and a lost lion cub are rescued by a girl in the heart of the Canadian wilderness. Their friendship will change their lives forever.